Pneumonia in Toddlers: Association of Characteristics and Nutritional Status - Elia Badriah; Indana Indana (Universitas Pendidikan Indonesia, 2021)
Pneumonia is one of the health problems that contribute to the mortality of toddlers. Pneumonia cases in children are determined by health history. The purpose of this study was to analyze the relationship between age, gender, birth weight, history of breastfeeding, nutritional status, and immunization status with the incidence of pneumonia in toddlers at the Kudus Aisyiyah Hospital. The design of this study was analytic observational with a cross-sectional approach. A total of 102 patients have participated as research respondents, and sampling was done using the accidental technique. The instrument used in this study is an observation sheet prepared for toddler patients with pneumonia. Data analysis was carried out using chi-square and fisher's exact method. The results showed that 48 patients (47.1%) had pneumonia. There was a significant relationship between the age of children under five (p=0.003) and birth weight (p=0.0001) with the incidence of pneumonia. There was no relationship between gender (p=0.399), exclusive breastfeeding (p=0.495), and nutritional status (p=0.141), with the incidence of pneumonia in children under five. The age variable is associated with the pneumonia incidence in toddlers at Kudus 'Aisyiyah Hospital. Mothers are expected to pay more attention to the health of their toddlers due to their vulnerability to a variety of diseases, particularly infectious diseases. Support and counseling programs from health workers were also expected to help mothers' understanding to improve their child's health quality.